Predation, prey preference and switching behaviour of the soil predatory mite Blattisocius mali (Mesostigmata: Blattisociidae) on immature stages of Drosophila hydei - Muhammad Arslan Ibrahim; Katarzyna Michalska; Marcin Studnicki (Experimental and Applied Acarology, 2026)
Blattisocius mali is a soil predatory mite known to disperse phoretically on adult drosophilid fruit flies and feed ectoparasitically on them during transport. Despite this association, its behavioural and trophic interactions with immature drosophilid stages remain poorly understood. This study analysed B. mali ’s ability to prey on Drosophila hydei immature stages and examined the effects of prior rearing diet on predation, prey preference, and switching. Two types of predatory mite were compared: (1) fly-reared (FR) and (2) mite-reared (MR), raised on fruit flies or acarid mites, respectively. Predator females successfully attacked all developmental stages, except pupae, during 24 h of exposure in our assay. In non-choice tests, mean predation rates were highest on first-instar (L1), followed by eggs, second-instar (L2), and third-instar larvae (L3). FR predators, as compared to MR predators, showed the highest predation rates on all prey stages except L3. Feeding on fly eggs, B. mali exhibited significantly higher fecundity, laying nearly twice as many eggs compared to when they were fed on L1. Their oviposition declined markedly on L2 and L3. In two-choice and three-choice assays, B. mali showed a clear preference for eggs over larval instars in both predator types. FR predators preferred L1 over L2, while, conversely, MR predators preferred L2. Furthermore, B. mali females displayed different behaviour depending on the proportion of fly eggs and/or larvae available, including no switching, switching, or counter-switching. These findings improve understanding of trophic interactions between mesostigmatic mites and drosophilid flies and highlight the role of dietary experience in shaping predator foraging behaviour.